Blue skies and black olives : a survivor's tale of housebuilding and peacock chasing in Greece - Humphrys, John (Hodder & Stoughton, 2009)
It was a moment of mad impulse when John Humphrys decided to buy a semi-derelict cottage and a building site on a plot of land overlooking the Aegean. A few minutes' gazing out over the most glorious bay he had ever seen was all it took to persuade him. After all, his son Christopher - a professional musician fluent in Greek - was already raising his family there so he would help build the beautiful villa that John dreamed of. What could possibly go wrong? Everything. John was to spend much of the next four years regretting his moment of madness. Some of it had its comic side. He learned to cope with the escaped peacock that took over his lemon grove and even a colony of rats that took over the cottage. Some of the humans proved trickier: the old man demanding payment for olive trees in the middle of John's own land; the unfriendly neighbour who tried to barricade him in and the friendly neighbour who dragged his lovely old fishing boat onto the beach and set fire to it after a row with his wife. And, of course, the builders. If you have ever struggled with builders, read this and be grateful. John learned a lot about Greece in a short time. He grew to love and lament the country and its people, but was never for a moment bored by them. And Christopher learned a bit more about John. Their shared experience revived keen memories for him of growing up with a father for whom patience was never the strongest virtue... Here father and son tell a story by turns hilarious and revealing about a country that intrigues and infuriates in equal measure.